Integrated arithmetic and basic algebra - Jordan, Bill E.; Palow, William P. (Boston, Massachusetts : Pearson, 2013)
Integrated Arithmetic and Basic Algebra, Fifth Edition, integrates arithmetic and algebra to allow students to see the big picture of math. Rather than separating these two subjects, this text helps students recognize algebra as a natural extension of arithmetic. As a result, students see how concepts are interrelated and are better prepared for future courses.
1. Adding and Subtracting Integers and Polynomials -- 2. Laws of Exponents, Products and Quotients of Integers and Polynomials -- 3. Linear Equations and Inequalities -- 4. Graphing Linear Equations and Inequalities -- 5. Factors, Divisors, and Factoring -- 6. Multiplication and Division of Rational Numbers and Expressions -- 7. Addition and Subtraction of Rational Numbers and Expressions -- 8. Ratios, Percents, and Applications -- 9. Systems of Linear Equations -- 10. Roots and Radicals -- 11. Solving Quadratic Equations.
Includes index.
Keywords: ARITHMETIC